Práticas de manejo para a sustentabilidade da produção agrícola em solo tropical coeso - Portela, Stefanny Barros (2021)
In the humid tropics, structurally fragile and cohesive soils are widely distributed, due to the combination of sedimentary material, high weathering and low levels of soil organic matter. In this region, plants explore water and nutrients only from a thin surface layer, which impairs biomass accumulation and crop productivity. Soil coverage combined with gypsum application has been indicated as an efficient strategy for improving soil physical structure, organic carbon accumulation and also increasing crop productivity in the humid tropics. Legume biomass can provide soil cover, retain moisture, favor microbial activity and provide nutrients, including nitrogen. While gypsum, due to its high solubility and high calcium content, has been indicated as an excellent alternative to retain organic carbon in the soil and improve aggregation and rooting. In this sense, our aim was to monitor the dynamics of organic carbon and cations in the radicular zone of a cohesion tropical sandy soil after the application of gypsum and legume residue to verify its period of stay at a critical level and to evaluate how this dynamics affects maize productivity. Our results suggest that mulch and gypsum, applied with urea, can increase soil rooting capacity, improve moisture retention, provide organic carbon, retain calcium in the soil profile and increase maize productivity. Therefore, in cohesive soils with a fragile structure, the combination of legume biomass and gypsum allows the maintenance of adequate levels of organic carbon and calcium in the root zone, which consists of a simple and advantageous strategy to be explored by farmers to increase the soil rooting capacity and crop productivity.